Listeria monocytogenes-induced gamma interferon secretion by intestinal intraepithelial gamma/delta T lymphocytes. - Yamamoto, S (1993)
gamma/delta T cells represent a major proportion of intestinal intraepithelial lymphocytes (IEL), and it has been suggested that these IEL serve as a first immune barrier against microbial invasion and that they do so by destroying infected epithelial cells. In the present study, we confirm that both alpha/beta and gamma/delta IEL from naive mice express potent cytotoxicity and produce gamma interferon (IFN-gamma) after T-cell receptor (TCR) engagement by specific monoclonal antibodies (MAb). Intraperitoneal administration of the anti-gamma/delta TCR MAb GL3 caused downregulation of the gamma/delta TCR in IEL, and IEL from gamma/delta TCR-modulated mice failed to express cytotoxic activity and to secrete IFN-gamma after gamma/delta TCR engagement. In contrast, alpha/beta IEL from such mice were still cytolytic and secreted IFN-gamma. Mice were infected orally with virulent Listeria monocytogenes at doses which caused bacterial invasion through the intestinal epithelia. Although alpha/beta and gamma/delta IEL from these mice expressed high cytolytic activities in antibody-redirected killer assays, target cells pulsed with listerial antigens were not lysed. In contrast, IFN-gamma secretion by IEL from L. monocytogenes-infected mice was induced not only by anti-TCR MAb but also by target cells pulsed with listerial antigens, whereas irrelevant antigens, including heat shock protein 60, did not induce IFN-gamma secretion. Furthermore, the number of IFN-gamma-secreting IEL, as assessed by the enzyme-linked immunospot technique, was increased during listeriosis. gamma/delta TCR modulation by GL3 administration abrogated antigen-induced IFN-gamma secretion by IEL from infected mice. These findings suggest that L. monocytogenes induced IFN-gamma secretion by gamma/delta IEL from mice suffering from intestinal L. monocytogenes infection and invasion. Thus, the data provide evidence for a role of IFN-gamma-secreting IEL in local resistance against listeriosis and perhaps other food-borne diseases.